Design and test of a new marine energy harvesting device - Ng, Ming Zher. (2012)
Vortex Induced Vibration (VIV) is a natural phenomenon that exists in many engineering situations with negative impact. In recent years, many studies have tried to utilize the catastrophic power into useful energy. The main objective of the project aims to design and develop a prototype that taps on hydro energy with VIVs. The report covers the design of a prototype, a parametric study, and evaluation on the experimental result. Furthermore, Computational Fluid Dynamics (CFD) simulations were employed to assist in the parametric study. The parametric studies cover amplitude ratio, velocity ratio, frequency ratio, and mass ratio. The amplitude ratio relative to velocity ratio locates velocity range where the best result of vibration can be obtained. The cut-in speed of the current prototype is 0.271m/s, whereas the maximum amplitude obtained is 63.78mm and above. The frequency ratio relative to velocity ratio provides useful insight on the synchronization of VIV. The current study shows an increasing trend of the frequency ratio across the velocity ratio. The relationship between amplitude ratio and mass ratio helps to determine the optimum structural mass in VIVs. The experimental result shows the amplitude ratio increases significantly as the mass ratio reduces across the velocity ratio. Lastly, the design of a power generator, which serves to convert mechanical motion into electrical energy, is discussed in the report for the further development.